House prices and ultra-low interest rates: Exploring the non-linear nexus - Daniel Dieckelmann; Hannah S. Hempell; Barbara Jarmulska; Jan Hannes Lang; Marek Rusnàk (European Central Bank (ECB), 2023)
The acceleration of house price growth amidst falling interest rates to record-low levels across euro area countries between 2015 and 2021 has sparked renewed interest in the link between the two variables. Asset-pricing theory suggests that real house prices respond to changes in real interest rates in a non-linear fashion. This non-linearity should be especially pronounced at very low real interest rates. Most existing empirical studies estimate models with a constant semi-elasticity, thereby ruling out by design the potential non-linearities between house prices and interest rates. To address this issue, we estimate a panel model for the euro area countries with a constant interest rate elasticity (as opposed to a constant semi-elasticity), which is consistent with asset pricing theory. Our empirical results suggest that, in a low interest rate environment such as the period between 2015 and 2021, non-linearities in the house price response to interest rate changes are important: an increase of real interest rates from ultra-low levels could lead to downward pressure on real house prices three to eight times higher than the literature suggests.
Keywords: E43; E52; R21; R30; 330; house prices; interest rates; elasticity; non-linearity